Strategi Pembelajaran Pendidikan Agama Islam dalam Membentuk Sikap Anti-Bullying Siswa: Studi Pustaka - Amia Kasmila; Agus Pahrudin; Nanang Supriadi; Ali Murtadho (WISE Pendidikan Indonesia, 2026)
This study aims to analyze Islamic Religious Education (PAI) learning strategies for developing students’ anti-bullying attitudes through a review of previous studies. Bullying in schools remains a significant concern because it can negatively affect students’ psychological well-being, social relationships, and learning environment. This study employed a qualitative approach using a library research method. Data were obtained from scientific journals, books, academic articles, and previous studies addressing PAI learning strategies, character education, and bullying behavior among students. Documentation was used as the data collection technique, while the data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that exemplary behavior (uswah hasanah), habituation of moral values, group discussions, integration of character education, and humanistic and communicative learning approaches play important roles in fostering anti-bullying attitudes. These strategies support the development of empathy, tolerance, responsibility, and mutual respect among students. Therefore, PAI serves not only as a medium for transmitting religious knowledge but also as a strategic instrument for character formation and bullying prevention. The study implies that schools and PAI teachers should systematically integrate anti-bullying values into classroom instruction, daily school routines, and student interactions to promote a safe, inclusive, and harmonious learning environment.